The Therapeutic Potential of Two Egyptian Plant Extracts for Mitigating Dexamethasone-Induced Osteoporosis in Rats: Nrf2/HO-1 and RANK/RANKL/OPG Signals - Samar R. Saleh; Omnia M. Saleh; Ashraf A. El-Bessoumy; Eman Sheta; Doaa A. Ghareeb; Saber M. Eweda (MDPI AG, 2024)
The prolonged use of exogenous glucocorticoids, such as dexamethasone (Dex), is the most prevalent secondary cause of osteoporosis, known as glucocorticoid-induced osteoporosis (GIO). The current study examined the preventative and synergistic effect of aqueous chicory extract (ACE) and ethanolic purslane extract (EPE) on GIO compared with Alendronate (ALN). The phytochemical contents, elemental analysis, antioxidant scavenging activity, and ACE and EPE combination index were evaluated. Rats were randomly divided into control, ACE, EPE, and ACE/EPE MIX groups (100 mg/kg orally), Dex group (received 1.5 mg Dex/kg, Sc), and four treated groups received ACE, EPE, ACE/EPE MIX, and ALN with Dex. The bone mineral density and content, bone index, growth, turnover, and oxidative stress were measured. The molecular analysis of RANK/RANKL/OPG and Nrf2/HO-1 pathways were also evaluated. Dex causes osteoporosis by increasing oxidative stress, decreasing antioxidant markers, reducing bone growth markers (OPG and OCN), and increasing bone turnover and resorption markers (NFATc1, RANKL, ACP, ALP, IL-6, and TNF-α). In contrast, ACE, EPE, and ACE/EPE MIX showed a prophylactic effect against Dex-induced osteoporosis by modulating the measured parameters and the histopathological architecture. In conclusion, ACE/EPE MIX exerts a powerful synergistic effect against GIO by a mode of action different from ALN.